Articulating Media Genealogy, Interface, Situation - Gabrillo, James (Open Humanities Press, 2023)
o 'articulate' media means to understand them by locating their connections in space and time. Articulating Media offers new approaches to the writing of technology and the technologies of writing by twinning an investigation of language with an attention to location. Where does media theory take place? How should media theory understand its own occupation of the spaces of media? What materialities might survive media's many articulations and associations? Diverse in topic and method, the collection's nine chapters analyse those questions of value, representation, and categorisation that are held within the languages of media. Contributors consider media technologies - following previous volumes in the Technographies series - not as mute objects addressed through language, but as processes and devices situated in the very grammars and vocabularies of their address. Scholars of literature, film, musicology, art, design theory, and media history evaluate new linguistic possibilities for thinking across disciplines and for considering the significance of location to media-critical writing. Collectively, the book traces the ways in which media vernaculars have shaped the vernaculars of media theory, and proposes a few ways in which we might reshape them.